2013
DOI: 10.1038/ki.2012.348
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease may be differentially diagnosed from preeclampsia by serum biomarkers

Abstract: Preeclampsia, affecting 5-8% of pregnancies, is the main cause of fetal-maternal mortality and morbidity. The differential diagnosis with chronic kidney disease (CKD) is a challenge owing to the overlapping clinical features. No biomarker has been found to discriminate between the two conditions. Here, we tested whether maternal serum levels of placental growth factor (PlGF) and soluble FMS-like tyrosine kinase-1 (sFlt-1), markers of preeclampsia, could be used to discriminate between 34 patients with preeclam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 23 publications
8
66
2
3
Order By: Relevance
“…Interestingly, none of the societies address this issue in their guidelines. However, the angiogenic markers (as mentioned above in Angiogenic Factors) sFlt-1 and PlGF have been shown to be able to distinguish preeclampsia from CKD (13,14) and thus, may be potentially incorporated in practice for more clarity.…”
Section: Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, none of the societies address this issue in their guidelines. However, the angiogenic markers (as mentioned above in Angiogenic Factors) sFlt-1 and PlGF have been shown to be able to distinguish preeclampsia from CKD (13,14) and thus, may be potentially incorporated in practice for more clarity.…”
Section: Guidelinesmentioning
confidence: 99%
“…Hence, the incorporation of angiogenic markers may help to risk stratify women with high suspicion for preeclampsia. Similarly, angiogenic markers have proved to be useful in distinguishing between confounding diagnoses, such as chronic hypertension, CKD, and lupus nephritis (12)(13)(14)(15). The potential to target sFlt as a therapy is also exciting and currently being studied using an apheresis technique (16).…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…[67][68][69][70][71] Angiogenic markers have also been shown to be promising in preeclampsia-related disorders, such as idiopathic fetal growth restriction and stillbirth. 72,73 To demonstrate clinical use of these biomarkers, we led a large clinical study to evaluate the role of angiogenic biomarkers in the prediction of preeclampsia-related adverse outcomes among women evaluated at our institution for suspected preeclampsia.…”
Section: Biomarker Studies In Preeclampsiamentioning
confidence: 99%
“…Several groups have shown that sFlt-1 and free PlGF levels can be used to differentiate preeclampsia from diseases that mimic preeclampsia, such as chronic hypertension, gestational hypertension, kidney disease, and gestational thrombocytopenia (Salahuddin et al 2007;Sunderji et al 2010;Perni et al 2012;Rolfo et al 2012;Verdonk et al 2012).…”
Section: Angiogenic Factors As Biomarkersmentioning
confidence: 99%